IMPLEMENTATION OF PACKAGING TYPES ON THE PHYSICOCHEMICAL CHANGES OF CABBAGE AND BOK CHOY - Nurjannah Nurjannah; Nurul Zakiyah (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
Pakcoy and Chinese cabbage can only last up to 3-4 days. One method to increase the shelf life and maintain the quality of these commodities is with proper packaging and storage techniques. In this study, the effect of the type of packaging on the shelf life and damage that occurs in pakcoy and Chinese cabbage commodities will be studied. This study used a Rancangan Acak Lengkap (RAL) with the type of packaging treatment factor. There are four types of packaging used, namely PP (Polypropylene Plastic), PE (Polyethylene Plastic), plastic wrappig and opaque paper. From the research results, it is known that packaging can maintain the quality or quality of mustard greens and pakcoy during storage. Chickpeas samples packaged with PP plastic experienced the lowest weight loss of 0.3%. Meanwhile, the unpackaged Chinese cabbage samples (control) experienced a weight loss of up to 43%. Pakcoy vegetables packaged in PE plastic packaging experienced the lowest weight loss of 9.1%. The unpackaged Chinese cabbage samples (control) experienced the highest weight loss, reaching 9.3%. This indicates that the packaging treatment was able to suppress damage and weight loss in Chinese cabbage and pakcoy.Keywords: Chinese cabbage, packaging, Polypropilene Plastic, Polyethylene Plastic.